2014
DOI: 10.3906/sag-1209-2
|View full text |Cite
|
Sign up to set email alerts
|

Review of clinical experience with acute cholecystitis on the development ofsubsequent gallstone-related complications

Abstract: Background/aim: Recently, surgery during admission has been advocated for acute cholecystitis, rather than delayed surgery after conservative treatment. This study was designed to perform early surgeries and analyze the criteria used for conservative management followed by delayed surgery. Materials and methods:After implementation of a study with the aim of performing early surgery, a retrospective review using a prospective database during the period of June 2009 to June 2011 was established. Early surgery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…Twelve articles described randomized clinical trials (RCTs), of which four reported on two trials, and there were four prospective studies and ten retrospective studies ( Table ). Only one randomized trial compared antibiotic treatment with conservative management without antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve articles described randomized clinical trials (RCTs), of which four reported on two trials, and there were four prospective studies and ten retrospective studies ( Table ). Only one randomized trial compared antibiotic treatment with conservative management without antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Only one randomized trial compared antibiotic treatment with conservative management without antibiotics. Twenty studies, including 11 RCTs and one prospective study, compared initial treatment with antibiotics and (early) cholecystectomy. Five were non‐comparative cohort studies that described the fate of patients initially treated with antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations